Proportional Reinsurance: Some comments on the more usual clauses used in obligatory contracts (Fire and Allied Perils) - Pearce, Eric A. (Assurances, 1975)
It is generally agreed, I believe, that Proportional Reinsurance was the original form of reinsurance and has been in common use for a very much longer time than has Excess of Loss Reinsurance or Stop Loss Reinsurance. It would therefore have been logical to have considered first of all the proportional methods for my series of notes on reinsurance, but it was as a matter of deliberate choice that I dealt first with Excess of Loss Reinsurance and then with Stop Loss Reinsurance. I felt that I might have something more to offer when commenting on the latter two methods than when writing about Quota Share and Surplus reinsurances, which have been the subject of standard contracts for a great many years, the original wordings having been modified from time to time, to meet changing conditions, but remaining basically the same. It is now some years since two insurance companies, one French and one British, made it known to those, such as myself, who are interested in these things, that the reinsurance contracts between them had been in existence for one hundred years, without interruption. We all like to think of reinsurance as being a long term business, but this must truly be a record. I have dealt here only with obligatory treaties which form the overwhelming majority of the business, in terms of premium income. Nevertheless, Facultative reinsurance continues to have great importance, and has systems, methods and conventions essentially its own.